2010
DOI: 10.1590/s1516-35982010000700011
|View full text |Cite
|
Sign up to set email alerts
|

Prolificidade de caprinos mestiços leiteiros no semiárido nordestino

Abstract: RESUMO -Utilizaram-se 526 registros de parições de cabras mestiças com o objetivo de avaliar a influência de alguns efeitos de ambiente sobre a prolificidade. As análises estatísticas foram realizadas por meio de modelos lineares generalizados, empregando-se a função de distribuição binomial e a função de ligação logística. As probabilidades de ocorrência de partos múltiplos foram calculadas por meio de um modelo que incluiu os efeitos de ano e mês de cobertura, ordem de parto, idade ao primeiro parto, peso à … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
3
4
0
4
Order By: Relevance
“…This is in agreement with the results of Sarmento et al (2010), who observed that higher nutritional level of females at the time of mating improved ovulation rates, resulting in higher prolificacy.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with the results of Sarmento et al (2010), who observed that higher nutritional level of females at the time of mating improved ovulation rates, resulting in higher prolificacy.…”
Section: Resultssupporting
confidence: 93%
“…This may be due to the higher number of primiparous goats in Anglo-Nubian and crossbred Boer breeds supplied with SL30, since the birth order affects prolificacy. The reproductive systems of primiparous females are not completely developed, which might cause abnormalities in female gametes, decreasing herd prolificacy (SARMENTO et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At parturition, fecundity was statistically similar (P > 0.05) between the groups, with an overall mean of 1.39 ± 0.11 kids, and there were no differences in the multiple birth rate between groups. Our findings were similar to those of Sarmento et al (2010), who reported a mean of 1.35 and 35.5% for litter size and multiple birth rate, respectively, in crossbred Alpine × Gurguéia reared in a semi-extensive system. Silva et al (2011) studied Anglonubian × SPRD goats in the same geographic area of the present experiment, and recorded values of 1.43 and 25% for litter size and twinning rate, respectively, which were very similar to the findings of our study.…”
Section: Resultssupporting
confidence: 91%
“…Ressalte-se a importância da fertilidade ao parto, da prolificidade e da sobrevivência, particularmente das crias no transcorrer do período de amamentação e na fase de recria (Medeiros et al, 2006;Sarmento et al, 2010). Entende-se que o desenvolvimento de crias caprinas durante o período de amamentação, particularmente no transcorrer do primeiro mês de vida, é estreitamente relacionado com a produção de leite da cabra.…”
Section: Introductionunclassified